Photometric and Spectroscopic Study of the Delta Scuti Stars FH Cam, CU CVn and CC Lyn - Conidis, G. J.; Gazeas, K. D.; Capobianco, C. C.; Ogloza, W. (Communications in Asteroseismology, 2010)
Three short period (P ∼ 1 day) variable stars from the Hipparcos catalogue targets were observed after suspected misclassification as Beta Lyr eclipsing systems (Perryman et al. 1997), as no secondary component had been noticed in the inspection of their Broadening Functions (BFs) (Rucinski 2002). FH Cam is found to be a multiple star system with a member exhibiting Delta Scuti behaviour. The dominant pulsation frequency is found to be 7.3411 ± 0.0002 c/d, which corresponds to a pulsation mode of l ≤ 1. We confirmed the pulsations of CU CVn using photometric observations and found a pulsation frequency of 14.7626 ± 0.0250 c/d, which is in agreement with the period given in literature. CC Lyn is a non-eclipsing visual binary (CCDM J07359+4302AB), the brighter component (A) is found to be a multi-mode Delta Scuti pulsator, with pulsation frequencies of 5.6402 ± 0.0004 c/d and 7.3368 ± 0.0005 c/d.